2009
DOI: 10.1590/s1020-49892009001200008
|View full text |Cite
|
Sign up to set email alerts
|

Quality and effectiveness of diabetes care for a group of patients in Colombia

Abstract: Despite high testing rates, metabolic control was not effective. Low rates of medication adjustment among patients with measures outside target ranges suggest the need for changes in routine diabetes care to ensure therapeutic regimens are adjusted appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
17
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 17 publications
6
17
0
7
Order By: Relevance
“…Furthermore, the DDD was not modified across follow‐up despite not reaching therapeutic goals, being even lower than recommended in some of the groups. Even so, the proportion of patients with metabolic control was similar to previous reports (30%–50%) …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the DDD was not modified across follow‐up despite not reaching therapeutic goals, being even lower than recommended in some of the groups. Even so, the proportion of patients with metabolic control was similar to previous reports (30%–50%) …”
Section: Discussionsupporting
confidence: 90%
“…Colombia is one of five Latin American countries with the highest number of cases of diabetes mellitus. Previous studies indicate that people with T2DM of Colombia has on average 62.4 years, mainly women (55.0%), with low education level, with overweight (44%) and obesity (30.2%) and is specially treated with metformin (71.5%) and insulin (28.5%) . The Colombian healthcare system (SGSSS) is accessible to all of the population and includes full access to human and analogue insulin.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study to assess quality and effectiveness of diabetes care for a group of patients in Colombia it was shown that only 6.9% of patients had achieved the goals recommended for control of glucose, lipids and blood pressure. 4 However such surveys are lacking in India and we do not have data regarding achievement of ADA recommendations in Indian setting.…”
Section: Introductionmentioning
confidence: 96%
“…4 In recently published data from a nationwide survey in United States during the period 2007e2010 out of a cohort of 4296 adults 20 years with diabetes, 52.5% of patient had HbA1c < 7%, 51% had BP < 130/80 mm Hg, 56.2% achieved LDL < 100 mg/dl and 18.8% achieved all three parameters. 10 …”
mentioning
confidence: 99%
“…El patrón de prescripción de las sulfonilureas dentro del arsenal terapéutico antidiabético se reporta con porcentajes variables: 26,7 y 56 % en Estados Unidos, 40% en Argentina, 58,2 y 64,9% en Colombia, subrayando que la sulfonilurea evaluada en Argentina y Colombia fue exclusivamente la glibenclamida [5][6][7][8][9] .…”
Section: Introductionunclassified